Treatment of corn seeds with biostimulant - Gonzaga, Benedito Alves; Andrade, Christiano Lima Lobo de; Cabral Filho, Fernando Rodrigues (Brazilian Journal of Science, 2023)
Biostimulants depending on the composition, when applied in the plant can be promoted a serie of structural changes and allow the plant to reach its biggest productive potencial. The corn when is stimulated its root system promotes a bigger nutrient absorption including nitrogen that is a key element in its productivity. The experiment was developed at Instituto Federal Goiano Campus Rio Verde – GO, Brazil, in the off-season 22/22. The treatments was composed taking account the application of biostimulant in seed’s treatment and planting in the ground. There were carried out reviews like: plants height, number of leaves, shoot dry weight, shoot green weight, root length, dry root weight, green root weight and chlorophyll. Through the found results it was possible to conclude that the used’s treatments doesn’t significantly influenced in evaluated variables, also more searches are necessary for corroborating or refuting the results found in this Search.